PENGARUH PEMBELAJARAN KOOPERATIF LEARNING BERBASIS APLIKASI KAHOOT TERHADAP HASIL BELAJAR IPS SISWA KELAS VIII SMPN 1 SEI BAMBAN - Anggi Ratulangi; Eka Susanti (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2025)
The IPS learning outcomes of students at SMPN 1 Sei Bamban are still classified as low and do not yet meet the Minimum Completeness Criteria (KKM). This is due to the lack of variation in the teaching models used byy the teachers, which makes the students passive during classroom learning. Therefore, the researcher implemented a cooperative learning model combined with the Kahoot application so that students would be actively involved both individually and in groups, with the hope of improving students learning based on the Kahoot application on students social studies learning outcomes. This is study uses a non-equivalent control group design. The research population consists of all students at SMPN 1 Sei Bamban, which comprises 8 classes. The research sample consisted of 64 students, with 32 students from class VIII-1 and 32 students from class VIII-2. The data collection method used pretest and posttest, and then the data were analyzed using SPSS Version 25.0 software. Based ob the hypothesis testing results using the Independent sample t-test, it was found that the average learning outcomes of the experimental class students were 84,88, while the control class students had an average of 75,75, with a significance value (sig) (2-tailed) of 0,000<0,05. Therefore, it can be concluded that there is an influence of the cooperative learning model based on the Kahoot application on the learning outcomes of students in the IPS subject at SMPN 1 Sei Bamban.